Is fluorometric sentinel lymph node biopsy in endometrial cancer necessary? - Huang, Liqiong; Cheng, Wei; He, Chenghui; Li, Xin; Huang, Lu; Zhang, Jiajia; Song, Liwen; Zhou, Yifan; Wang, Chenchen; Gan, Xiaoqin; Qiu, Jin (Frontiers in Medicine, 2024)
Objective: In this study, we collected perioperative and postoperative follow-up data from patients with endometrial cancer (EC) at different stages to evaluate the role of SLNB in endometrial cancer surgery.Methods: 186 endometrial cancer patients undergoing radical hysterectomy from January 2018 to April 2022 were retrospectively analyzed. Patients were classified into four groups. Group A comprised patients diagnosed with stage IA grade 1 and 2 endometrioid EC who underwent SLNB.Group B comprised patients with stage IA grade 1 and 2 endometrioid EC who did not undergo SLNB. Group C comprised patients with higher-grade endometrioid EC, wherein systematic lymph node dissection was performed based on SLNB results. Group D comprised patients with higher-grade endometrioid EC who did not undergo SLNB and instead underwent direct systematic lymph node dissection. Clinical, pathological data, and follow-up information for all patients were collected.In Group A, SLNB was performed on 36 out of 67 patients with IA stage 1 and 2 endometrial cancer, yielding a SLN positivity rate of 5.6%. There were no significant differences observed between the two groups regarding perioperative outcomes and postoperative follow-up.Conversely, among 119 patients with higher-grade endometrial cancer, 52 underwent SLNB, with 20 patients exhibiting SLN positivity, resulting in a SLN positivity rate of 38.4%. However, the decision to undergo SLNB did not yield significant differences in perioperative outcomes and postoperative follow-up among these patients.For stage IA grade 1 and 2 endometrioid EC, the incidence of lymph node positivity is low, omitting SLNB in this subpopulation is a feasible option. In other stages of endometrioid EC, there is no significant difference in perioperative and postoperative follow-up data between patients undergoing routine systematic lymphadenectomy and those undergoing systematic lymphadenectomy based on SLNB results. Therefore, if SLNB is not available, the standard procedure of PLND remains an option to obtain information about lymph node status, despite the surgical complications associated with this procedure.